Aatujeevitham - Benyamin (Green Books Private Limited, 2008)
Aadujeevitham, by Benyamin, is a novel that blends together perfectly sweetness of prose, a premise steeped in life-experience, and the Malayali ethos. The captivating beauty of the desert, the specialties of the underworld world... none of this has been recorded so deeply in Malayalam prior to this. This novel has raised Malayalam Literature and the language to new heights. In its artistic and beguiling/seductive experience, Benyamin's novel Aadujeevitham compares favorably with Shantaram by Gregory David Roberts. Aadujeevitham is not a piece carved out of life, rather it is a blood-filled part of life itself. Not only sympathetic readers, but persons from all walks of life should read this novel.